Partisipasi Siswa Dalam Mnegikuti Dzikir Pagi di SMPN 1 Koto Salak - Ramadhayani, Arlin (Jurnal Sakinah, 2022)
The study was based on participation, activation, enthusiasm for students following the dzistinginess which of all the students does not participate in the morning dzscrooge. The study aims to see why many of the students who didn’t participate in following the dzclosed-morning approaches help to use data retrieval techniques by interviews and observation and data-gathering techniques using the reduction of data presentation and education data withdrawal.The result of this study indicate that some of your students remain inactive beacause of the laziness of children. Being enthusiastic about following dzcrooge this morning is still short because many students are talking to their friends and following dzscrooge. While students’ obedience to the rules made by the school is so lax that many are late.